SUSTAINABLE DIGITAL MARKETING STRATEGY IN THE PERSPECTIVE OF SUSTAINABLE DEVELOPMENT GOALS - Hidayat, Muhamad; Salam, Rahmat; Hidayat, Yogi Syarif; Sutira, Andri; Nugrahanti, Trinandari Prasetyo (KOMITMEN: Jurnal Ilmiah Manajemen, 2022)
The idea of sustainable development goals has become a catchphrase for many cutting-edge organizations due to its universal application. Many governmental and nongovernmental organizations (NGOs) and businesses throughout the world are actively focusing on this idea, but a thorough definition of the concept that encompasses digital marketing is lacking. The advent of digital marketing has revolutionized the way businesses interact with their global clientele. More and more businesses are realizing that the digital environment is not just the present, but also the future of their industry. When looking at the big picture, businesses think about how they can keep expanding and maintaining their current model. Sustainable digital marketing tactics are the focus of this research, which will examine them in light of global development targets. This study takes a descriptive qualitative approach. In light of the findings of this study, we sustainable development means providing for current needs without jeopardizing future generations' potential to do the same. Here, marketing is crucial, both in terms of emphasizing the importance of applying this concept and in terms of aligning company strategy with the environment. As a result, organizations now rely heavily on digital marketing to disseminate and communicate their ongoing actions and to get insight into how users behave and interact with them on the Internet.